2019
DOI: 10.1021/acscatal.8b04919
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Computational Study of the Cu-Catalyzed Hydration of Alkenes in Water Solvent and into the Context of an Artificial Metallohydratase

Abstract: Despite the increasing efforts in the last few years, the identification of efficient catalysts able to perform the enantioselective addition of water to double bonds has not been achieved yet. Natural hydratases represent an interesting pool of biocatalysts to generate chiral alcohols, but modifying their substrate scope remains an issue. The use of artificial metalloenzymes (ArMs) appears as a promising solution in this field. In the last few years, Roelfes and co-workers have been designing a variety of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Schematic representation of the modeling study to decode LmrR-Phen-Cu­(II) water mediated hydration mechanism . Top: The surface of the entire ArM is represented in blue with the catalytic site out and in ball and stick representation.…”
Section: Recompilation Of Arm Modeling Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic representation of the modeling study to decode LmrR-Phen-Cu­(II) water mediated hydration mechanism . Top: The surface of the entire ArM is represented in blue with the catalytic site out and in ball and stick representation.…”
Section: Recompilation Of Arm Modeling Resultsmentioning
confidence: 99%
“…Combining protein−ligand dockings and MD simulations, we used the near-to-catalysis pregeometric criteria to select MD snapshots as starting point of large full-QM cluster calculations to simulate the enantiospecific hydration pathways. 52 This integrative approach showed that the origin of the enantioselectivity was related to a negatively charged residue D100 in the binding pocket, an amino acid identified experimentally as the major ee promoter (Figure 5).…”
Section: Decoding Arm Catalytic Mechanismsmentioning
confidence: 99%
“…The DFT level of theory and RESP model to assign the atomic charges were selected following the protocol proposed to derive AMBER and TIP3P force fields for molecular dynamics (MD). 27 …”
Section: Computational Sectionmentioning
confidence: 99%
“…Point charges of the complete POMs were derived with the RESP (Restrained ElectroStatic Potential) model. The DFT level of theory and RESP model to assign the atomic charges were selected following the protocol proposed to derive AMBER and TIP3P force fields for molecular dynamics (MD) …”
Section: Computational Sectionmentioning
confidence: 99%
“…Nevertheless, many different reactions have been targeted by chemists looking to develop more sustainable catalysts that utilise water as a solvent, low temperatures and allow metal recycling (see Figure 1C-E for examples) [23][24][25][26][27]. ArMs have also begun to provide solutions for reactions where small molecule catalysts have not achieved the desired selectivity [28,29].…”
Section: Recent Advancesmentioning
confidence: 99%